EVALUATION OF ELISA AS AN ALTERNATE ASSAY TO SERUM NEUTRALIZATION TEST FOR QUANTIFICATION OF RABIES SPECIFIC ANTIBODIES IN DOGS - Swapna Susan Abraham; Meera Unwin Antony; P.M. Prasad (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The study evaluated a widely used commercial ELISA as a potential alternate to serum antibody assay under field conditions for measurement of rabies specific antibodies in canine sera. The comparison of ELISA with RFFIT, an approved neutralization method, showed a concordance of 53.3% for identifying sero converted animals (≥0.5IU/ml) with sensitivity of 41.6% and specificity of 100%. In the different titre groups, maximum concordance (100%) was found in medium titre range (2-4 IU/ml) and differed considerably in very low or high titre groups. In the study, ELISA demonstrated its potential as an alternative tool to antibody assays to check if the animal has developed rabies-specific antibodies. This study recommends more trials with larger sample frame to ascertain its usefulness.